Education Sector Open Government: A Bibliometric Analysis - Erdayani, Rizki; Afandi, Syed Agung; Afandi, Muslim (Indo-MathEdu Intellectuals Journal, 2024)
The aim of this research is to analyze open government bibliometrics in the education sector. Education is one of the most popular fields in open government. This research uses a qualitative approach with bibliometric analysis methods. The data used is secondary, obtained from the Scopus database. Data was collected using Publish or Perish with the keyword education sector open government. The data obtained was then selected using OpenRefine and analyzed using VOSviewer to obtain a bibliometric map generated from keywords throughout the paper. Based on the results of this research, there have been 160 papers in the last 51 years. The first open government paper on the education sector was published in 1972. There are 17634 citations, 75 h-index, and 126 g-index, which shows this paper has high impact and productivity. In this paper, there are 153 keywords grouped into 13 clusters. From these keywords, 1878 total link strengths and 663 occurrences were obtained. The keywords that dominate this paper are open policy making, social auditing, open contracting, and open budgeting. This shows that open government studies in the education sector focus on these issues.